THE DIFFERENCE OF PAIN SCORE RESULT AFTER USING VISUAL ANALOGICAL SCALE AND VERBAL RATING SCALE AMONG CHILDREN OF POST-SURGERY IN BHAYANGKARA HOSPITAL, MAKASSAR - Rusli Taher (Stikes Graha Edukasi Makassar, 2019)
Introduction: The research aimsto identify the different score result in using the Visual Analogical Scale (VAS) and Verbal Rating Scale (VRS) among children of the post-surgery in Bhayangkara Hospital, Makassar. Method: The research used the cross-sectional study approach. The research samples was 19 children and selected by using the Nonprobability sampling technique of the purposive sampling technique. Data were collected by using the standard operational procedure sheet. The data were analyzed with univariate and bivariate analyses, distribution table, and statistical test of Paired T-Test with the significance level of 95%. Results: There are difference results of pain scores between VAS and VRS scales in postoperative among children, paired t test the value of sig p = 0,000 is obtained. Conclusion: The research result indicates that there is the difference of the pain mean score between the visual analogical scale and the verbal rating scale.